Human Development and Mental Health: A Comparative Case Study of Indonesia and Singapore [Pembangunan Manusia dan Kesehatan Mental: Studi Komparatif Indonesia dan Singapura] - Firman Daud Lenjau Lung (Universitas Pelita Harapan, 2023)
Mental health has been a subject of growing discussion for the past years. However, there is still an ongoing debate as to how it has been incorporated into the human development discussion, especially in the Southeast Asia region that mostly consisted of economically growing countries. This paper chooses Indonesia and Singapore to see the disparities and commonalities between the two countries in integrating mental health into their strategy and to what extent it has affected their human development. To answer the question, this paper utilises a combination of qualitative and quantitative data derived from the Human Development Index (HDI) from UNDP and other reports that constitutes the accessibility of mental health infrastructure to the general public. Despite the ongoing assumption that countries with higher HDI have better mental health coverage, the finding of this study illustrates how both in Indonesia and Singapore, access to mental health is heavily circumscribed. The growing awareness of people towards mental health problems is not being acquainted with proper response from stakeholders, namely the government; and sociocultural shift that eliminates stigmatisation surrounding the sufferers.Bahasa Indonesia Abstract: Kesehatan mental telah menjadi topik perbincangan yang hangat dalam beberapa tahun terakhir. Namun, masih terdapat beragam perdebatan mengenai bagaimana kesehatan mental dapat diintegrasikan dalam diskusi pembangunan manusia, khususnya di kawasan Asia Tenggara yang sebagian besar terdiri dari negara berkembang. Artikel ini memilih Indonesia dan Singapura untuk melihat perbedaan dan persamaan antara kedua negara dalam mengintegrasikan kesehatan mental terhadap strategi mereka dan sampai sejauh mana dapat memengaruhi pembangunan manusia mereka. Untuk menjawab pertanyaan penelitian, artikel ini menggunakan kombinasi data kualitatif dan kuantitatif yang berasal dari Human Development Index (HDI) dari UNDP dan laporan lainnya yang menjelaskan daya akses infrastruktur kesehatan mental bagi khalayak umum. Meskipun terdapat asumsi yang mengatakan bahwa negara dengan HDI yang lebih tinggi memiliki cakupan kesehatan mental yang lebih baik, temuan dari artikel ini menggambarkan bagaimana di Indonesia dan Singapura akses terhadap kesehatan mental sangat dibatasi. Kesadaran orang yang semakin tinggi terhadap masalah kesehatan mental tidak dibarengi dengan tanggapan yang tepat dari pemangku kepentingan, khususnya pemerintah, dan pergeseran sosial-budaya yang menghapus beragam stigma di sekitar para penderita.